Healthcare providers' perspectives on the acceptability and uptake of HPV vaccines in Zimbabwe. (1st October 2016) - Crann, Sara E.; Barata, Paula C.; Mitchell, Rachel; Mawhinney, Leah; Thistle, Paul; Chirenje, Zvavahera Mike; Stewart, Donna E.
Abstract: Background: Human papillomavirus (HPV) vaccines are a critical strategy in the prevention of cervical cancer, especially in countries like Zimbabwe where cervical cancer screening rates are low. In Zimbabwe, cervical cancer is the leading cause of cancer-related deaths in women but the HPV vaccine is not yet widely available. This study examined healthcare providers': (1) perceptions of current hospital practices and issues in cervical cancer prevention and treatment in Zimbabwe; (2) knowledge of HPV and HPV vaccines; and (3) perspectives on introducing HPV vaccination programs in Zimbabwe, including potential facilitators and barriers to successful implementation. Method: In-depth semi-structured interviews were conducted at a rural hospital with 15 healthcare providers in Zimbabwe. Interviews included eight main questions and a number of additional probes that reflected the study's purpose. Data were analyzed using thematic analysis. Results: Participants reported that women are not consistently being screened for cervical cancer. There were generally low levels of knowledge about HPV and HPV vaccines, but participants asked many questions indicating a desire to learn more. Although they were highly supportive of implementing HPV vaccination programs in Zimbabwe, they also identified a number of likely psychosocial, cultural, and logistical barriers to successful implementation, including cost, vaccine schedule, and hospital infrastructure. However, participants also provided a number of culturally relevant solutions, including education and community engagement. Conclusion: This study provides insight from healthcare providers about barriers to implementation and possible solutions that can be used by policy makers, practitioners, and other stakeholders to facilitate the successful implementation of forthcoming HPV immunization programs in Zimbabwe.